Viabilidade técnica da substituição do vergalhão de aço pelo vergalhão de fibra de vidro em vigas de concreto armado submetidas à flexão - Teixeira, Victória Angeli (2024)
The constant quest for innovative solutions results in more efficient materials with lesser environmental impact. With high resistance to corrosion, oxidation, and magnetism, GFRP bars emerge as one such solution. While more commonly used in non-structural elements and with limited research on this composite in structural elements, the study aims to analyze the feasibility of replacing steel rebars with this composite in reinforced concrete beams. For this purpose, a total of seven reinforced concrete beams with a cross-section of 8 cm x 16 cm and a length of 1.63 m were fabricated, with three of them reinforced with steel and four with GFRP, and tested under four-point bending, with central displacement measured using a displacement gauge. It was concluded that when directly compared, i.e., considering the same areas of steel and GFRP, beams reinforced with steel have an average deformation 29% lower than those reinforced with GFRP, in addition to supporting a load approximately 67% higher.